Synthesis, In Vitro and In Silico Bacteriostatic Evaluation of Halogenated Triazene Derivatives - Ainaa Nadiah, Abd Halim; Davlye Noissy, Diosing; Nor Hisam, Zamakshshari; Zainab, Ngaini; Yeo, Kai Wei; Aina Syakirah, Mohammad Hussin (Springer Nature, 2024)
This study explores the potential of paracetamin, an amine derivative of paracetamol, pronounced for its versatility as an intermediate for dye synthesis and biological application in addressing bacterial resistance. Here, a new series of halogenated triazene derivatives obtained through N-coupling reactions of paracetamin with halogenated aniline derivatives at ortho, meta, and para positions with a moderate yield of 19–72% were discussed. Antibacterial activity of these compounds evaluated against Staphylococcus aureus and Escherichia coli via Kirby–Bauer disc diffusion method observed that four of the compounds bearing fluoro-, chloro-, and bromo-substituents at meta as well as para-bromo substituted triazene displayed a great inhibition zone of 9–12 mm against both strains with ampicillin as its positive control. The structure–activity relationship through molecular docking analyses on CrtM and DNA gyrase enzymes revealed the binding scores of –7.1 to –8.3 and –8.3 to –8.6 kcal/mol respectively, highlighting the significant contribution of hydrogen bonding, hydrophobic and van der Waals interactions towards the binding affinity. Furthermore, the drug-likeness potential of the compounds was assessed through in silico ADMET and Lipinski’s rule of five where all compounds adhere and screened to have great pharmacokinetics properties, and low toxicity of 0.360–0.682 for particularly bromo substituted triazene derivatives outlining their potential drug bioavailability.